(3CSGSjGJ EOGQI GdehGO hGdEeOGO (B/s - (3Mfaj, YHO GdZaGQs; (3bQbGU, QSejIs ((3GdbGgQI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2002)
(3GdeaGgje GdCSGSjI dEOGQI GdEeOGO(B-(3hXjaI GdTQGA(B-(3SjGSI GdTQGA(B-(3WQb GdTQGA hOhQI GdTQGA(B-(3GdeNGRf hhXjaI GdJNRjf(B-(3GdJfXje GdOGNdj ddeNGRf(B-(3GdQbGHI Ydi GdeNRhf hJbjje GdCOGAs
Keywords: (3GOGQI GdeNGRfs; (3GOGQI GdeTJQjGJs; (3GdTQGAs